2016
DOI: 10.1039/c6ra03197h
|View full text |Cite
|
Sign up to set email alerts
|

Antenna-type radiofrequency generator in nanoparticle-mediated hyperthermia

Abstract: This study covers the employment an antenna-type RF generator modulus at varying powers for different nanoparticle types to evaluate viability, apoptosis and necrosis of L-929 fibroblast and MCF-7 breast cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Heat generating by using RF wave in the presence of metallic nanoparticles was studied in our previous work [11]. RF (144.00015 MHz, 180 W) exposed to the nanoparticles revealed that the highest heat rate records in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heat generating by using RF wave in the presence of metallic nanoparticles was studied in our previous work [11]. RF (144.00015 MHz, 180 W) exposed to the nanoparticles revealed that the highest heat rate records in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the RF hyperthermia, the external energy is in the form of RF waves around megahertz (MHz) domain. Despite the advantages such as less harmfulness, high-tech level and costeffectiveness, some other factors should be considered including the wave focusing on target, the SAR index as well as the penetration depth [8] should be considered as a potential disadvantageous [9][10][11]. The other notable factors that can be marked are nanoparticles morphology and the efficient RF wavelength that needed to provide the activation energy [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, AuNPs were prepared according to the well-known citrate-reduction method with some modifications, which was shown in our earlier reports [34][35][36][37][38][39]. Briefly, the proper amount of aqueous solution of HAuCl 4 (50 mL, 1 mM) in a three-neck round bottom flask was heated to boiling under vigorous magnetic stirring.…”
Section: Synthesis Of Agnps and Aunpsmentioning
confidence: 99%
“…In recent years, the research work involving nanoparticles in cancer treatment has been actively conducted in a wide range of areas, such as drug-delivery, 3,4 imaging contrast agents 5,6 and hyperthermia agents. [7][8][9][10][11][12] These methods are designed to enhance the specificity, in the meantime without introducing negative side effects.…”
Section: Introductionmentioning
confidence: 99%